Intelligent Computing for Big Data - Wang, Wei; Man, Ka Lok (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Recent advances in artificial intelligence have the potential to further develop current big data research. The Special Issue on 'Intelligent Computing for Big Data' highlighted a number of recent studies related to the use of intelligent computing techniques in the processing of big data for text mining, autism diagnosis, behaviour recognition, and blockchain-based storage.